2019
DOI: 10.1002/pmrj.12255
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Iliotibial Band Strain under Different Knee Alignments

Abstract: Background: Increased strain of the iliotibial band (ITB) is a plausible contributing factor for the development of iliotibial band syndrome (ITBS). Although several studies have found relationships between the strain of the ITB and kinematic factors during running, the associations of the ITB strain with knee alignment and sex, which are considered intrinsic factors, are not well understood.Objective: To clarify the sex differences in the ITB strain between genu varum and normal knee alignments in different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Findings of this study should be interpreted in light of some limitations. First, the majority of participants were females, and differences in morphological and biomechanical features may have a different impact on displacement and mechanical properties of the ITB (Fain et al, 2019; Hannigan et al, 2018; Kim et al, 2020). This limits the potential to extrapolate findings into a broader population.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of this study should be interpreted in light of some limitations. First, the majority of participants were females, and differences in morphological and biomechanical features may have a different impact on displacement and mechanical properties of the ITB (Fain et al, 2019; Hannigan et al, 2018; Kim et al, 2020). This limits the potential to extrapolate findings into a broader population.…”
Section: Discussionmentioning
confidence: 99%
“…Increased muscle stiffness in runners might lead to false negative SWE values as compared to healthy volunteers. Moreover, another very recent study showed that women with genu varum alignment exhibit higher ITB strain during weight-bearing, which could be related to a higher incidence of ITBS in women [37]. This was unknown to us prior to this study's subject selection and therefore not evaluated and should be addressed in further studies.…”
Section: Limitationsmentioning
confidence: 95%
“…The etiology of ITBS involves both intrinsic and extrinsic factors (6,7), and the risk factors for ITBS include past history, static and dynamic alignment in the lower extremities, and gender (8). Previous studies have identified that excessive motion of the hip and knee in the frontal and transverse planes are important factors in the development of ITBS (6,9,10).…”
Section: Original Articlementioning
confidence: 99%